Evaluasi Penerapan Sistem Akuntansi Pendapatan Pada Badan Keuangan Daerah Kota Lubuklinggau - Miki Indika; Abdika Jaya; Novi Septianah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
The aim of this study is to evaluate the application of an income accounting system to the Regional Finance Body of Lubuklinggau City. It is descriptive research; this research is not intended to test hypotheses but only systematically describes the facts, situations, and activities of the accounting system of income in the Regional Finance Agency of the City of Lubuklinggau. Operational variables of this study are income accounting systems with related party indicators, related documents, and accounting systems and procedures. Secondary data is in the form of body profiles and reports on the realization of regional revenue and expenditure budgets. The data analysis technique used descriptive analysis. The results of the study showed that the income accounting system at the Lubuklinggau City Regional Finance Body for related parties is not appropriate with Government Regulation Number 71 of 2010, PERMENDAGRI Number 64 of 2013, and Regulation of Lubuklinggau Mayor, Number 63 of 2016 and Regulation Lubuklinggau Mayor Number 32 of 2012.It had been already referring to Government Regulation Number 71 of 2010 concerning Regional Financial Management Guidelines, and for related documents and systems and procedures for accounting income in accordance with Government Regulation Number 71 of 2010, PERMENDAGRI Number 64 of 2013, Regulation of Mayor of Lubuklinggau Number 63 of 2016 and Regulation of Mayor Lubuklinggau Number 32 of 2012.